IMPLEMENTATION OF THE ONE ISLAMIC BOARDING SCHOOL ONE PRODUCT (OPOP) PROGRAM POLICY IN REALIZING CHAMPION ISLAMIC BOARDING SCHOOLS IN WEST JAVA - Ali, Muhamad; Pratmaningsih, Sri Astuti (Multifinance, 2024)
This article aims to review literature related to the One Pesantren One Product (OPOP) Program as a strategy for realizing the economic empowerment of Islamic boarding schools in West Java. The research method used is qualitative. This approach involves interviews with Islamic boarding school leaders and members of the surrounding community to gain an in-depth understanding of the vision, goals, and challenges in implementing the OPOP program. The results of this study show that the role of the West Java provincial government is adaptive and innovative in realizing the OPOP program in West Java, and this program has an impact on economic empowerment for the Islamic boarding school community in West Java. This literature review concludes that the One Pesantren One Product (OPOP) Program in West Java has successfully empowered the community in Islamic boarding schools through innovative economic activities.